An off-the-shelf decellularized and sterilized human bone-ACL-bone allograft for anterior cruciate ligament reconstruction. (November 2022) - Uquillas, Jorge Alfredo; Spierings, Janne; van der Lande, Antonio; Eren, Aysegul Dede; Bertrand, Manon; Yuan, Hao; Yuan, Huipin; van Groningen, Bart; Janssen, Rob; Ito, Keita; de Boer, Jan; Foolen, Jasper
Abstract: Approximately 1% of active individuals participating in sports rupture their anterior cruciate ligaments (ACL) every year, which is currently reconstructed using tendon autografts. Upon reconstruction, clinical issues of concern are ACL graft rupture, persistent knee instability, limited return to sports, and early onset of osteoarthritis (OA). This happens because tendon autografts do not have the same compositional, structural, and mechanical properties as a native ACL. To overcome these problems, we propose to use decellularized bone-ACL-bone allografts in ACL reconstruction (ACLR) as a mechanically robust, biocompatible, and immunologically safe alternative to autografts. Here, a decellularization protocol combined with sterilization using supercritical carbon dioxide (scCO2 ) was used to thoroughly decellularize porcine and human ACLs attached to tibial and femoral bone blocks. The specimens were named ultrACLean and their compositional, structural, and mechanical properties were determined. Our results indicate that: 1) decellularization of ultrACLean allografts leads to the removal of nearly 97% of donor cells, 2) ultrACLean has mechanical properties which are not different to native ACL, 3) ultrACLean maintained similar collagen content and decreased GAG content compared to native ACL, and 4) ultrACLean is not cytotoxic to seeded tendon-derived cells in vitro . Results from an in vivo pilot experiment showed that ultrACLean is biocompatible and elicits a moderate immunological response. In summary, ultrACLean has proven to be a mechanically competent and biocompatible graft with the potential to be used in ACLR surgery. Highlights: Decellularization and scCO2 sterilization maintain the mechanical characteristics of human bone-ACL-bone allografts. Decellularized and sterilized ACL tissue shows excellent in vitro cell proliferation and biocompatibility. Decellularized and sterilized ACL tissue shows a controlled inflammatory response after ACL reconstruction surgery in pigs. Graphical abstract: Image 1